Wage dispersion and technical progress - Agénor, Pierre-Richard 1957-; Aizenman, Joshua 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
Since the early 1980s, wage dispersion and the ratio of skilled to unskilled employment have increased significantly in several industrial countries. A number of economists have attributed these trends to skill-biased technical progress. This paper studies the wage and employment effects of technological changes of this type. The analysis is based on a model with a heterogeneous work force and a segmented labor market. Skill-biased technical progress is modeled as a shock that switches demand from unskilled to skilled labor in the primary, high-wage sector, while leaving the total demand for labor in that sector constant at initial wages. Such a shock reduces total employment in the primary sector, as the equilibrium increase in skilled labor employment is smaller than the fall in employment of unskilled labor. Efficiency factors are shown to magnify the adverse employment effects of pro-skilled technical change.